Compressive Strain Sensing Elastic Foam Based on Sericin Dispersed Carbon Nanotubes. Issue 1 (1st January 2023) - Li, Ming; Xiao, Ming; Jiang, Weidong; Ran, Jianhua; Min, Yuhuan; Yang, Tong; Bi, Shuguang; Xia, Long
Abstract: The flexible strain sensor can transform the micro or macro deformation into the visual electrical signals for monitoring the physiological and motor characteristics of human body. However, the current commercial strain sensors generally have some shortcomings such as large stiffness and small strain range. In this work, a flexible compressive strain sensor with the 3D conductive network was fabricated by using biomacromolecule sericin protein dispersed carbon nanotubes (SSCNTs) as the conductive material and melamine foam (MF) as the elastic matrix. The results showed that the sensitivity of MF/SSCNTs elastic foam was 1.36 in the strain range of 0-70% with the CNTs content of 10 wt% and the cyclic compressive sensing performance was stable for at least 1600 cycles. This kind of flexible compressive strain sensor is environmentally friendly, low cost, simple process, and provides a new method for the preparation of green flexible sensor.